Changes in the composition of the soil seed bank of grassland after giant ragweed (Ambrosia trifida L.) invasion. (1st September 2022) - Wang, Hanyue; Liu, Tong; Dong, Hegan; Zhao, Wenxuan; Liu, Xuelian; Wang, Ruili; Xu, Wenbin
Abstract: Giant ragweed ( Ambrosia trifida L.), an invasive weed, has an expanding distribution area and has recently started to spread in grasslands. This unusual event threatens grasslands worldwide. In this study, we aimed to evaluate the changes in the grassland soil seed banks caused by the giant ragweed invasion in Yili Valley, Xinjiang, China. Using the space-for-time substitution approach, we compared and quantified the soil seed bank communities in a grassland over eight years following giant ragweed invasion and after its removal. The results showed that the duration of invasion determined whether giant ragweed might pose a significant threat to the native seed bank community. Four years after the invasion, the in-site seed bank density of native community significantly decreased (30.44%), while the relative coverage of giant ragweed aboveground reached 83.75%. Furthermore, the species richness in the seed bank decreased significantly (12.36%), while the relative coverage of giant ragweed reached 100% six years after the invasion. Eight years after the invasion, the seed bank density and species richness of the native community decreased by 83.28% and 39.33%, respectively, whereby the seed banks tended to be homogeneous. After the removal of giant ragweed, the potential for regeneration was limited by the residual seed bank densities of the native community. Although the native seed bank density had increased significantly after three years of restoration, new growth was dominated by weedy species, rather than by the distinctive components of the grassland habitat. Our study clarifies the process by which giant ragweed causes damage to grasslands and serves as a reference for grassland restoration and management efforts. Graphical abstract: Image 1 Highlights: Giant ragweed can reduce plant species diversity when it invades grasslands. Giant ragweed can change the soil seed bank composition of grassland community in a short time. Removal of giant ragweed leaves a legacy of invasion.